DAMPAK PENAMBANGAN EMAS TERHADAP KUALITAS AIR SUNGAI SINGINGI DI KABUPATEN KUANTAN SINGINGI PROVINSI RIAU - T Iskandar Johan; Ediwarman Ediwarman (Program Pascasarjana Universitas Riau, 2011)
This study was conducted in March until August 2008. The research site is the Singingi riverwaters Petai rural areas (upstream) to the village of Tanjung pauh (downstream) subSingingi Downstream, Kuantan Singingi District, Riau Province. Metode used in this study isa survey method. The analysis in this study is done by using descriptive analysis.Implementation of the analysis performed on Singingi river waters that includes physical andchemical parameters such as temperature, brightness, turbidity, current speed, water depth,TSS, O2, pH, CO2, BOD5, COD, Nitrate and Phosphate. The results showed that goldmining can make Singingi river waters are at a fairly alarming rate in a state that has beencontaminated between the categories of mild contaminated with heavy contamination. It canbe seen from the results of laboratory analysis of physical and chemical parameters of thelevel of pollution has passed the threshold value (MAB) in accordance with the PP. 82 In2001, about Managing water quality and water pollution control such as brightnessparameter (9.0 to 19.0 cm.), Turbidity (139.40 to 199.27 NTU), TSS (86.33 to 115.96 mg / l).,BOD5 (14 to 16.6 mg / l) and COD (138.91 - 143.31 mg / l) has exceeded the qualitystandards of water quality